Changes in Patient-reported Swallow Function in the Long Term After Chemoradiotherapy for Oropharyngeal Carcinoma. Issue 12 (December 2018) - Martin, A.; Murray, L.; Sethugavalar, B.; Buchan, C.; Williams, G.F.; Sen, M.; Prestwich, R.J.D.
Abstract: Aims: To assess long-term patient-reported swallow function after chemoradiotherapy for oropharyngeal carcinoma and to evaluate the frequency of deterioration/improvement over years. Materials and methods: Fifty-nine patients with oropharyngeal carcinoma treated with parotid-sparing intensity-modulated radiotherapy and concurrent chemotherapy between 2010 and 2012 had previously completed the MD Anderson Dysphagia Inventory (MDADI) at a median of 34 months (range 24–59) after treatment. An MDADI was posted to 55 alive and disease-free patients after a 30 month interval; 52/55 replies were received, a median of 64 months (range 52–88) after treatment; 27/52 (52%) had been managed with a prophylactic gastrostomy. A 10 point or greater change in the MDADI scores was defined as clinically significant. Results: Overall, in the whole cohort, patient-reported swallow function showed a small absolute improvement in MDADI composite score on the second MDADI questionnaire (>5 years after treatment) compared with the first MDADI (>2 years after treatment); mean 68.0 (standard deviation 19.3) versus 64.0 (standard deviation 16.3), P = 0.021. Using the composite score, swallow function was stable over time in 29/52 (56%) patients; a clinically significant improvement in swallow function over time was noted in 17/52 (33%) patients; conversely 6/52 (12%) patients experienced a clinically significant deterioration with time. Abnormality of pre-treatment diet and a prophylactic gastrostomy correlated with an inferior MDADI composite score on the later questionnaire ( P = 0.029 and P = 0.044, respectively). Conclusions: Long-term dysphagia is prevalent >5 years after treatment. Although long-term swallow function is stable in most patients, it is not static in a minority. On MDADI composite summary scores, 33% of patients experienced an improvement, whereas 12% deteriorated with time. Further investigation is needed to determine underlying mechanisms behind these divergent outcomes. Highlights: Long-term dysphagia is a major morbidity after chemoradiotherapy. Patient-reported swallow outcomes assessed >2 and >5 years after chemoradiotherapy. Patient-reported swallow outcomes were stable in most patients. Divergent outcomes in minority with improvement in 33% and deterioration in 12%.